Tourism-Induced Environmental Degradation ASEAN Countries: Causes and Consequences - Fafurida, Fafurida; Solihah, Didah Mardiatin; Marpaung, Grace Natalia (International Journal of Energy Economics and Policy, 2025)
The existence of digitalization and technological advancements causes information to spread quickly. In fact, information about the tourism sector among countries like ASEAN is very easily accessible, which leads to an increase in people's mobility for tourism activities. ASEAN is one of the regions in the Asia Pacific with the highest CO2 emissions. Tourism is considered to be an important indicator in explaining a country's environmental pollution. This is based on the Tourism-Led Growth hypothesis, which states that the expansion of tourism activities impacts economic growth, while on the other hand, the Environmental Kuznets Curve hypothesis explains that economic development triggers environmental degradation. This study aims to analyze the influence of GDP per capita, the number of international tourists, and the volume of international flight passenger traffic on CO2 emissions and the relevance of the EKC hypothesis in 5 ASEAN countries (Indonesia, Malaysia, the Philippines, Thailand, and Vietnam). The data processing method uses panel data regression analysis. The selected model in this study is the fixed effect model with cross-section weight estimation. The results of the study indicate that GDP per capita and the volume of international flight passenger traffic have positive coefficients with probabilities of 0.0000 and 0.0171, respectively. Meanwhile, the number of foreign tourist visits has a negative coefficient with a probability of 0.0216. This study also shows that the EKC hypothesis is relevant to the case of the 5 ASEAN countries with a turning point at an income level of USD 9,937 per capita.